Multiple Paragangliomas Affecting Carotid Body and Vagal Region: A Case of Rare Occurrence - Bakshi, Jaimanti; Goyal, Atul Kumar; Vir, Dharam; Panda, Naresh K (Medical Science: Trends and Innovations Vol. 3, 2025)
Paragangliomas are neuroendocrine tumors that represent 0.012% of all tumors. Paragangliomas arise from extra-adrenal paraganglia, microscopic islands of cells derived embryonically from the neural crest cells of the autonomic nervous system. Paragangliomas are rare neuroendocrine tumors also known to occur in head and neck regions and generally involve the carotid body or vagal region. To date, only a single study has reported the occurrence of paragangliomas involving both the carotid body and vagal region. The present study, to our best knowledge, is the second study in the world which reported multiple paragangliomas involving the carotid body and vagal region. The patient in the present case study was a 45-year-old male with a single swelling in the left upper part of the neck. The patient was informed about the possible neural dysfunction with associated hoarseness, vocal change, aspiration, dysphagia, dysarthria, facial asymmetry, and shoulder weakness in addition to the possibility of a cerebrovascular accident. In the pre-operative clinical examination, the swelling was identified as a carotid body tumor, and the patient was then planned for surgery. The intra-operative findings revealed that it involved both the vagal and carotid body and was subsequently operated successfully. Post-operatively the swelling was described as bilateral carotid paragangliomas with left vagal paraganglioma. The patient was treated successfully with the surgery and recurrence was not reported in two years to follow-up. The present study will help clinicians in designing treatment strategies for such complicated cases of multiple paragangliomas.